Verbs of the subject’s movement and object’s movement as the «compensators» of semantics of perception verbs in Russian and Belarusian languages - Kraskouski, Mikalai I. (Journal of the Belarusian State University. Philology, 2019)
The Russian and Belarusian verbs of the subject’s movement and object’s movement are analyzed, which can be used as functional-text verbs of perception. The groups of verbs of the subject’s movement and the object’s movement in Russian and Belarusian languages and the basic verbs of these groups are described. Semes are named, on the basis of which words as functional-text verbs are included in the functional-semantic groups of the Russian and Belarusian verbs of perception.